PENGARUH PELATIHAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (COACH) DI EDISON LEARNING CENTER LUBUKLINGGAU - Catur Windaryadi; Surajiyo Surajiyo (Jurnal Media Ekonomi (JURMEK), 2020)
The purpose of this study was to determine partially and simultaneously the Effect of Training and Organizational Commitment on Employee Performance (coach) at the Edison Learning Center Lubuklinggau. This study data taken from direct respondents using a questionnaire instrument. The sample of this research is 37 people. The results of hypothesis testing with simple linear regression found the results that there is an effect of training on employee performance (coach) by obtaining the value of simple linear regression equation Y '= 33,638 + 0,873X, correlation coefficient 0.871, t test obtained value of tcount 10.487> t table 1.687, and Sign. 0,000 <0.05, the results of hypothesis testing with simple linear regression found that there was an influence of organizational commitment to employee performance (coach) by obtaining the value of simple linear regression equation Y '= 26.418 + 1.664X, correlation coefficient 0.834, t test obtained value tcount 8,936> table 1,687, and Sign. 0,000 <0.05 and While the results of hypothesis testing with multiple linear regression found that there was a significant influence of training and organizational commitment on employee performance (coach) by obtaining the value of the multiple linear regression equation Y '= 21.812 + 0.564 + 0.869, the coefficient of determination 0.924 , F test obtained fcount 98,774> ft. 3,25, and Sign 0,000 <0,05.